Faktor- Faktor yang Mempengaruhi Kemandirian Merawat Kaki Pada Pasien Diabetes Mellitus Tipe II - Nova Nurwinda Sari; Herlina Herlina (Indonesian Journal of Nursing Research (IJNR), 2018)
Diabetic foot problems are still the cause of death in several developing countries and prevalence of diabetes mellitus is thought to increase in the next decade in several countries. Adult clients with diabetes mellitus are seen as individuals who have the ability to care for themselves to make ends meet, maintain health and prosper. The ability of self-care in patients with type II diabetes mellitus causes patients to be able make efforts to control type II DM so that this condition can reduce acute and chronic complications. The purpose of this study was to find out the factors that influence the independence of caring for the feet. Type of quantitative research, analytic design cross sectional approach. The samples was type II DM patients with inclusion criteria : willing to be respondents in the study and agreeing to informed consent, can be invited to communicate verbally and understand Indonesian, suffer from type 2 diabetes mellitus, have nut and are not experiencing diabetic foot ulcer and are still carry out their own activities. The number of samples was 36 respondents with purposive sampling technique. Data collection is done by distributing questionnaires to samples included in the work area of the Sukarame Health Center. The analysis carried out was univariate analysis, and multivariate analysis (logistic regression test). The results of the study with logistic regression test found that gender is the variable which is the most influential factor affecting the independence variable caring for the foot with a p value of 0.043. In an effort to improve the independence of foot care, it needs to be done gradually starting from regular education and being introduced early in patients with diabetes mellitus as an effort to prevent diabetic ulcers. In other than, that it needs motivation both the family and health workers to improve their ability to carry out self-care, especially in foot care.